ESTIMATION OF POWER LOSSES DURING WORK OF COMMUNICATION NETWORK - J. V. Slad (Научный вестник МГТУ ГА, 2016)
A method over of estimation of power losses, arising up during work of communication networks is brought in this article. The traditional methods of similar estimation do not take into account inevitable power losses, related to the delay of signal, disсreet of changeable parameters and errors in the chain of management work of the system. The detailed analysis of laws of distributing is resulted for the different canals of connection.